2018
DOI: 10.3389/fpubh.2018.00209
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Is Associated With Antibody Levels Against Vaccine Preventable Diseases in the Netherlands

Abstract: Background: We investigated whether low socioeconomic status (SES), which is associated with reduced health and life expectancy, might play a role in increased risk for infectious diseases. Therefore, we explored the association between SES and immunoglobulin G (IgG) levels against various pathogens.Methods: We analyzed the association between SES [educational level and net household income (NHI)] and serum IgG concentration against measles, mumps, rubella, varicella, Haemophilus influenzae type B (HiB), pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
(45 reference statements)
0
10
0
1
Order By: Relevance
“…For many of the predictors included in the original QCovid model (contributing to risk prediction in an unvaccinated population during wave 1), the magnitude of the relative risks is broadly comparable in both QCovid2 (risk prediction in an unvaccinated population, wave 2) and QCovid3 (risk prediction in a vaccinated population, wave 2). Although these associations cannot be given a causal interpretation, individual characteristics such as age, 23 obesity, pre-existing medical conditions, and socioeconomic disadvantage 24 are known to affect immune competence 25 and, at least for certain diseases, affect the response to some vaccines [26][27][28][29][30] or to immunosuppressive drugs. 7 31 The associations with Down's syndrome in all the models are likely to reflect increased susceptibility to infection and genetic predisposition.…”
Section: Principal Findingsmentioning
confidence: 99%
“…For many of the predictors included in the original QCovid model (contributing to risk prediction in an unvaccinated population during wave 1), the magnitude of the relative risks is broadly comparable in both QCovid2 (risk prediction in an unvaccinated population, wave 2) and QCovid3 (risk prediction in a vaccinated population, wave 2). Although these associations cannot be given a causal interpretation, individual characteristics such as age, 23 obesity, pre-existing medical conditions, and socioeconomic disadvantage 24 are known to affect immune competence 25 and, at least for certain diseases, affect the response to some vaccines [26][27][28][29][30] or to immunosuppressive drugs. 7 31 The associations with Down's syndrome in all the models are likely to reflect increased susceptibility to infection and genetic predisposition.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Lower socioeconomic status is associated with seropositivity for CMV [ 60 , 61 ]. In the general population, suicide risk is also associated with lower socioeconomic status [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since CMV infection is transmitted through contact with infected body fluids, hygiene and hence socioeconomic status are important risk factors for CMV acquisition. The influence of education/literacy on CMV acquisition could be explained by the direct relationship between education and income which determines living conditions [59][60]. A study in Tanzania found urban residence to be a risk factor for CMV seropositivity when compared to rural residence [38].…”
Section: Socio-economic Statusmentioning
confidence: 99%